Identity without boundaries: Public administration's canon (s) of integration - Raadschelders, Jos C.N. (2010)
It is often charged that the study of public administration lacks boundaries and suffers from an identity crisis. This charge is grounded in a positivist belief in the unity of knowledge. From the perspective of positivists, the study of public administration lacks the epistemological unity that should make it a true science. Regarding public administration as an interdisciplinary study and practice makes it possible, indeed necessary, to include all theories, models, and concepts in use and not just those that are recommended and pursued by positivists. A conceptual map of knowledge integration efforts in public administration illustrates why public administration cannot, and should not be, a traditional academic discipline but rather must be understood as an interdisciplinary study and practice. - Reproduced.
Keywords: Public administration